Persepsi Harga Dan Fasilitas Pada Kepuasaan Pengunjung Di Marawa Beach Club Di Kota Padang - Maria Magdalena,; Widya Permatasari, (Jurnal Publikasi Ilmu Manajemen, 2023)
Based on the formulation of the problem in this study is how the influence of price perception on visitor satisfaction at Marawa Beach Club in Padang City and how the influence of facilities on visitor satisfaction of Marawa Beach Club in Padang City. This type of study uses quantitative methods, data collection through the distribution of questionnaires to 100 respondents with the sampling used in this study is non-probability sampling with accinndetal sampling techniques. By using instrument tests, validity tests and reality test, deskriprif tests, classical assumption tests normality tests, multicollinearity tests and heteroschidasticity tests then multiple linear regression and hypothesis tests with the help of SPSS applications. The results of the study show that price perception has a positive and significant effect on visitor satisfaction and facilities have a positive and significant effect on visitor satisfaction. So it can be concluded in this study found that the variables of price perception and facilities have a positive and significant effect on visitor satisfaction at Marawa Beach Club in Padang City. Where the calculated t value is greater than the table t.